2020
DOI: 10.3389/fpsyg.2020.570644
|View full text |Cite
|
Sign up to set email alerts
|

Does Trauma Shape Identity? Exploring the Links Between Lifetime Trauma Exposure and Identity Status in Emerging Adulthood

Abstract: In emerging adulthood, coherent identity plays a protective role against the development of the disturbed psychosocial functioning and is seen as one of the defining characteristics of positive youth development. The factors that shape the identity are still understudied and little quantitative research has addressed, how trauma exposure is linked to emerging adults' identity. Therefore, the current study aimed to investigate how exposure to traumatic experiences over the lifetime is associated with current id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Given the different physical, social and cultural contexts, it is not surprising that adolescents in Japan and Lithuania are differentially exposed to potentially traumatic experiences. First, we found that the majority of adolescents were exposed to traumatic experiences in Lithuania, in line with the previous studies on adolescents and youth (Kazlauskas et al ., 2020; Truskauskaite-Kuneviciene et al ., 2020). However, only less than half of the adolescents in Japan reported exposure to traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…Given the different physical, social and cultural contexts, it is not surprising that adolescents in Japan and Lithuania are differentially exposed to potentially traumatic experiences. First, we found that the majority of adolescents were exposed to traumatic experiences in Lithuania, in line with the previous studies on adolescents and youth (Kazlauskas et al ., 2020; Truskauskaite-Kuneviciene et al ., 2020). However, only less than half of the adolescents in Japan reported exposure to traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of all traumatic experiences was used to estimate cumulative trauma exposure. The Lithuanian version of LEC-R was used in several studies previously ( Kvedaraite et al, 2020 ; Truskauskaite-Kuneviciene et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, exposure to traumatic experience was considered if participants responded with either 1 (= “happened to me”) or 2 (= “witnessed it”). The Lithuanian version of LEC-5 has been validated and used earlier ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%